(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigates waste management practices in restaurants in the Sunyani Municipality in Ghana. The objectives of the study are to classify the types of solid waste generated by restaurants and assess the readiness of restaurants to adopt waste reduction, reuse, and recycling practices. Design/Methodology/Approach: The study employed a descriptive cross-sectional approach with a sample of 331 restaurants. Simple random sampling was used to select the sample size. Structured questionnaires and observations were used. Descriptive statistics were employed in the review of the data to address the research questions formulated to direct the study. Specifically, percentages, frequencies, means, and standard deviations were used to analyse the questionnaire items. Findings: The findings reveal diverse waste types: liquid, solid, and gaseous generated by restaurants. The study’s findings reveal that waste management in the food service industry within the Sunyani Municipality is highly influenced by restaurant size and operational capacity. Larger restaurants tend to adopt more sustainable practices, such as portion control and waste minimisation, due to the financial and operational incentives available to them. However, many restaurants have yet to adopt paperless technologies for waste reduction. The readiness of smaller restaurants to engage in waste reduction and recycling efforts is still constrained by limited resources and logistical challenges. Research Limitation: The study’s reliance on self-reported data from restaurant managers and staff through questionnaires. Practical Implication: The study’s findings offer actionable strategies for improving waste management within the restaurant industry. Social Implication: The study emphasises how efficient waste management in the restaurant business may have a positive impact on public health. Originality/Value: This study addresses knowledge gaps in current waste management by exploring the factors that both promote and hinder sustainability in Ghana’s food service industry, specifically focusing on waste management practices in Sunyani restaurants. It offers new insights into the readiness to reduce, reuse and recycle solid waste, an area that has not been extensively researched.